A practical SCADA testbed in electrical power system environment for cyber-security exercises - Jamil N.; Qassim Q.; Daud M.; Abidin I.Z.; Jaaffar N.; Kamarulzaman W.A.W. (Institute for Mathematical Research (INSPEM), 2023)
Critical infrastructures; Cryptography; Electric power systems; Electric power transmission networks; Legacy systems; Public works; SCADA systems; Security of data; Testbeds; Critical infrastructure systems; Cyber security exercise; Electric power grids; Electrical power system; SCADA security; Security countermeasures; Unintended consequences; Vulnerability assessments; Electric power system security